Copula Omission in Down Syndrome. Issue 1 (2nd January 2023) - Christodoulou, Christiana; Wexler, Kenneth
ABSTRACT: This paper explores the nature of copula omission in Cypriot Greek individuals with Down Syndrome (DS). Previous studies on DS have attributed high rates of copula omission to an overall grammatical/inflectional impairment without offering further analysis. In order to identify relevant conditioning factors, we examined copula productions and omissions from spontaneous and elicited experimental tasks under five levels of analysis: categorial type of the predicate (nominal vs. adjectival), aspectual interpretation of the predicate (permanent vs. temporary), and a combination of these first two, as well as subject status (overt vs. covert) and experimental design (spontaneous vs. elicited). Results showed that adults with DS had significantly higher rates of copula omission than TD children. We found subject overtness to be the most reliable predictor of copula omission. A comparison of the two experimental methods of data collection also revealed a significant effect. Following an analysis based on the Unique Checking Constraint, we propose that copula omission is facilitated by the restriction that only one EPP feature (either the one in TP or the one in TopicP) can be checked. We discuss the implications of these results in the context of a distinction across a delayed vs. deviant development of the DS grammar.